Utilization of Alternative Buffer Solutions for Staining Thin Blood smears by the Giemsa, Wright stain and Romanowsky method - Neni Oktiyani; Ahmad Muhlisin; Erfan Roebiakto; Wahdah Norsiah; Mahpolah Mahpolah (Baiman Bauntung Batuah Center, 2023)
To make a reliable diagnosis on haematological examination, it is necessary to examine further the morphology of the blood cells previously stained in the procedure for staining thin blood smears using a buffer solution with a standard pH of 6.4 to 6.8. One of the problems that may occur in the laboratory is that the buffer reagents are damaged, past the expiration date or running out, so alternative buffers are needed that are cheap, fast and easy to obtain. This study aims to evaluate the staining results from alternative buffers. Study used a quasi-experimental method, and using alternative buffers from bottled mineral water following SNI-01-0553 2006. The colour produced by some of these alternative buffers is almost equivalent to blood cells stained with phosphate buffer. The percentage of assessment results in the alternative buffer codes B, C, D, E and F compared with control (A) were 62.67%, 92.00%, 82.67%, 80.00% 88, 00%, and 68.00%. The use of alternative buffers for staining thin blood smears using the Giemsa, Wright stain, and Romanowsky method can be done with mineral water as an alternative buffer for sample codes C, D, E and F, while B and G cannot be used. This alternative buffer can be applied by laboratory personnel in urgent situations in limited equipment and material facilities.